Abdominal surgery process modeling framework for simulation using spreadsheets. Issue 1 (August 2015) - Boshkoska, Biljana Mileva; Damij, Talib; Jelenc, Franc; Damij, Nadja
Highlights A framework for an abdominal surgery process simulation is proposed. The framework uses Activity table modelling technique and spreadsheets. The framework gives the state of each process activity at any point of time. It is easy read, possibly to upgrading and extend with other activities and models.